(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Unemployment is one of the major problem that Nigeria is battling with in the face of rising population and economic instability. This research evaluate the impact of Gross Domestic Product, Population Growth and Foreign Direct Investment on the rate of Unemployment. Annual data from the World Bank Open Data spanning from 1991- 2021 were used. Quantile Regression was used for the analysis and results revealed that Gross Domestic Product although not significant impacted negatively on unemployment. Population Growth and Foreign Direct Investment both negatively and significantly impacted on Unemployment thereby reducing the rate of Unemployment. Government should focus more on attracting foreign direct investment, increasing Gross Domestic Product and maximizing the ever growing population to control the rate of unemployment in the country.